2004
DOI: 10.1053/j.spid.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of infectious diseases among international pediatric travelers: Considerations for clinicians

Abstract: An estimated 1.9 million children travel overseas annually. Infectious disease risks associated with international travel are diverse and depend on the destination, planned activities, and baseline medical history. Children have special needs and vulnerabilities that should be addressed when preparing for travel abroad. Children should have a pretravel health assessment that includes recommendations for both routine and special travel-related vaccination; malaria chemoprophylaxis, if indicated; and prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 52 publications
0
10
1
1
Order By: Relevance
“…The data also indicated that P falciparum acquired in sub-Saharan Africa was the most common infection and that VFR children accounted for a majority of cases. 2,10,18 In contrast to studies in adults, no increased risk was found for male gender. 27 Dengue fever and enteric fever were the mostfrequently identified specific causes of systemic febrile illnesses among pediatric travelers returning from tropical regions other than subSaharan Africa.…”
Section: Figurecontrasting
confidence: 49%
See 1 more Smart Citation
“…The data also indicated that P falciparum acquired in sub-Saharan Africa was the most common infection and that VFR children accounted for a majority of cases. 2,10,18 In contrast to studies in adults, no increased risk was found for male gender. 27 Dengue fever and enteric fever were the mostfrequently identified specific causes of systemic febrile illnesses among pediatric travelers returning from tropical regions other than subSaharan Africa.…”
Section: Figurecontrasting
confidence: 49%
“…1 Although estimates of the number of children traveling internationally are limited, travel data for US residents in 2000 indicated that 7% of travelers (1.9 million travelers) were children. 2 Tourism is the major reason for travel but, as a result of growing global migration, children often accompany caregivers on trips visiting friends and relatives (VFR) abroad. [3][4][5] Although children represent a significant proportion of the traveling public, little information is available regarding health problems of children traveling internationally.…”
mentioning
confidence: 99%
“…73 Water should be boiled for at least 1 minute at altitudes <2000 m and 3 minutes at >2000 m. 56 Carbonated drinks also are considered safe for drinking, but water used to make ice can be contaminated. Safe water sources include bottled water from a trusted source or water that has been boiled, chemically treated, or filtered.…”
Section: Preventive Measuresmentioning
confidence: 99%
“…La vacuna conjugada, en relación con la vacuna de polisacáridos, probablemente tiene mayor duración, menor número de hiporrespondedores con las dosis de recuerdo y mayor efecto sobre la eliminación de portadores [50][51][52][53][54][55] . La Tabla 3 describe las vacunas contra la meningitis tetravalente 5,46,55 Indicaciones de vacunación en el niño que viaja: en EE. UU se recomienda Menveo® entre los 9 meses de vida y los 55 años, con revacunaciones cada 3-5 años, en función de la edad a la que se haya administrado la primera dosis y la continuidad del riesgo 50 .…”
Section: Consideraciones De Edad Respecto a La Vacuna Tetravalenteunclassified